The Impact of Supreme Court Decision Number 5851 K/Pid.Sus LH/2024 on Legal Certainty in Illegal Mining Cases - Febryani, Evy; Pahrijal, Rival; Zulfikri, Agung (Westscience Press, 2025)
This study analyzes Supreme Court Decision Number 5851 K/Pid.Sus LH/2024 and its impact on legal certainty in illegal mining cases in Indonesia through a normative juridical approach. The decision marks an important milestone in the enforcement of environmental criminal law, particularly in addressing unlicensed mining activities that cause ecological damage. By examining statutory regulations, judicial precedents, and doctrinal principles, this study reveals that the Supreme Court consistently applies the principles of strict liability and lex certa, emphasizing that illegal mining constitutes a criminal offense regardless of intent. The Court’s interpretation aligns with environmental protection objectives under Law Number 32 of 2009 and the Mining Law, promoting judicial consistency and strengthening environmental governance. The findings indicate that the decision enhances legal certainty by clarifying criminal liability standards, unifying judicial interpretation, and reinforcing the deterrent effect of environmental law. However, practical challenges remain in ensuring consistent enforcement, improving community awareness, and coordinating between central and regional authorities. Overall, this decision contributes significantly to the development of environmental jurisprudence and the realization of sustainable justice in Indonesia’s legal system.